Living law: jewish political theology from Hermann Cohen to Hannah Arendt - Vatter, Miguel E. (Oxford University Press, 2021)
Introduction : what is Jewish political theology? -- Philo and the origins of Jewish political theology -- Hermann Cohen and socialist democracy -- Franz Rosenzweig and religious constitutionalism -- Gershom Scholem and the mystical foundations of authority -- Leo Strauss and the concrete order of law -- Hannah Arendt and federalism -- Conclusion : the empty throne : from theocracy to anarchy.